Re-engaging Concepts of Professionalism to Inform Regulatory Practices in Nursing - Cusack, L.; Drioli-Phillips, P.G.; Brown, Janie; Hunter, S. (Elsevier, 2019)
Introduction It is important to define and promote professionalism because nurses’ conduct is at the heart of maintaining safe patient care and public trust in the profession. Professionalism and being professional are terms used frequently and interchangeably in the nursing literature and policy documents to describe qualities and conduct expected of nurses. However, there is not a shared understanding of the attributes of nursing professionalism.